2017
DOI: 10.1002/gps.4826
|View full text |Cite
|
Sign up to set email alerts
|

Self‐perceptions of aging mediate the longitudinal relationship of hopelessness and depressive symptoms

Abstract: As hypothesized, change in self-perceptions of aging partially mediated the relationship of hopelessness with depressive symptoms 6 years later. Findings are consistent with a conceptualization of hopelessness as broad negative expectations about the future that may contribute to negative self-perceptions of aging and subsequent changes in depressive symptoms. Reducing hopelessness, increasing hope, and improving self-perceptions of aging have potential to reduce and prevent depressive symptoms for older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The second largest HANC subgroup accounted for an average 14% in both samples. Older adults in the HANC subgroup had the highest level of Chronic‐Timeline and ER beyond depressive symptoms, supporting the previously identified link between negative SPA and depression using the variable‐centred method 16,50 . Consistent ageing awareness or ageing beliefs were found to be maladaptive and associated with increased depressive symptoms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The second largest HANC subgroup accounted for an average 14% in both samples. Older adults in the HANC subgroup had the highest level of Chronic‐Timeline and ER beyond depressive symptoms, supporting the previously identified link between negative SPA and depression using the variable‐centred method 16,50 . Consistent ageing awareness or ageing beliefs were found to be maladaptive and associated with increased depressive symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…Depression is one of the most important mental health concerns; approximately 22.3% of older adults in China have been reported as having depressive symptoms 14 . Several studies revealed that SPA directly or indirectly predicted the onset and persistence of depressive symptoms 15,16 . For example, the odds of belonging to the depressed ageing group rose by 17% because of a one‐unit increase in negative SPA 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In the mental-illness domain (outside of work environments), 95.5% of the 44 studies and 93.2% of the 88 associations found evidence of ageism influencing psychiatric conditions. The most frequently examined condition, depressive symptoms, showed evidence that ageism was associated with onset and lifetime depression, as well as increases in depressive symptoms over time [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. Reflecting a hopeful finding in this area, researchers found that when older persons resisted negative age stereotypes, they were less likely to experience suicidal ideation, anxiety, and PTSD in a nationally representative sample of American veterans [84].…”
Section: Impact Of Ageism On Health Of Older Persons: Individual Levelmentioning
confidence: 99%
“…Prior research also suggests variations in control beliefs and age perceptions by race/ethnicity (Assari, 2017;Ayalon, 2018). We controlled for education because having more years of schooling is related to lower negative SPA and more sense of control (Gum & Ayalon, 2018;Mitchell et al, 2018). We also adjusted for self-rated health because better health is associated with more positive perceptions of aging (Beyer et al, 2015) and a higher sense of control (Lachman & Firth, 2004).…”
Section: Sociodemographic Informationmentioning
confidence: 99%